Brazilian nuclear-powered submarine: National defense and technological externalities - Israel de Oliveira Andrade; Márcio Magno de Farias Franco e Silva; Giovanni Roriz Lyra Hillebrand; Luiz Gustavo Aversa Franco (Institute for Applied Economic Research (ipea), 2020)
In order to prepare and employ naval power and contribute to national defense, the Brazilian Navy, through its programs and projects, seeks to develop means of implementation of naval war operations and actions suitable for its main tasks - sea denial and control, and power projection. A significant portion of these efforts is the Submarine Development Program (PROSUB), which the ultimate purpose is to develop the first Brazilian nuclear-powered submarine. This paper aims to emphasize the importance of PROSUB (especially regarding the nuclear submarine) to the accomplishment of the Brazilian Navy constitutional mission and to the country's development and security, notably stressing its positive externalities (in technological, human resources and social terms) and the importance of its continuity and enhancement.
Keywords: F5; H56; L64; 330; Submarine Development Program (PROSUB); Brazilian nuclear-powered submarine; national defense; geopolitics; defense industry; Defense Industrial Base (DIB); Blue Amazon; maritime power; public policies; Brazilian Navy